HUBUNGAN ANTARA KADAR ETANOL, KADAR GULA REDUKSI DAN JUMLAH SEL DALAM PRODUKSI BIOETANOL DARI AIR KELAPA KENTALDENGAN PENAMBAHAN TWEEN80TM - Meisela, Elsy '; Restuhadi, Fajar '; ', Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study was conducted to determine the best concentration of Tween80™  in the manufacture of bioethanol from coconut water condensed by Saccharomyces cerevisiae. This study withincreasingthe urea and Tween80™ varying concentrations of this study conducted an experiment with four treatments and measurement in duplicate. Concentration of Tween80 ™ were T10 (0%), T2 (0.1%), T3 (0.2%) and T4 (0.3%). Observations were made every 24 hours; including ethanol content, sugar content and the number of cells. Data were analyzed descriptively by using a tabulation and graphs. The best treatment was a combination of T2 (urea 0.4 g / l and 0.1% Tween80™), which produced the largest ethanol 12%. Keywords: Coconut Water, Tween80™, Saccharomyces cerevisiae, Bioethanol, Veryhigh gravity